Radiosurgery for multiple brain metastases in non-small cell lung cancer – paradigm shift - Laranja, André (Medical imaging and radiotherapy journal, 2021)
Purpose: The purpose of this paper is to present a case of multiple brain metastases treated with LINAC-based radiosurgery (SRS). Materials and methods: Case report and a summary review of pertinent literature regarding SRS for multiple brain metastases. Results / Case Study: This case presents a patient with nonsmall cell lung cancer diagnosed with nine brain metastases who was treated with SRS. During follow-up, all brain lesions showed complete response with minimal impact on the patient’s quality of life. Discussion and Conclusion: The role of SRS is expanding, and recent published trials have showed promising results supporting its use in patients with more than four brain metastases. As our case suggests, SRS can be an eff ective and safe treatment for these patients and should be considered by physicians when they are presented with a similar case.
Keywords: brain metastases; metastaze v možganih; radiokirurgija; radiosurgery; radioterapija; radiotherapy